Digital Skills on One Health for Gen Z: Pemberdayaan Mahasiswa Lintas Disiplin melalui Literasi Digital dan Edukasi Kesehatan di Kampung Hobong, Papua - Sokoy, Fredrik; Assa, Inriyanti; Yesaya Samay, Izak; Innah, Herbert; Yufuai, Agustina R; Rumbiak, Helmin; Pariaribo, Konstantina M; Tuturop, Katarina L (The Community Engagement Journal, 2025)
The rapid development of information technology has created both opportunities and challenges in public health promotion, especially for Gen Z. This community engagement project, conducted by the One Health Collaboration Center at Universitas Cenderawasih, aimed to enhance digital literacy and health promotion skills among university students and the community in Hobong Village. A total of 88 participants, including 30 university students from diverse disciplines and 58 villagers, participated in a series of offline training and field surveys. The activities included training in video editing, Open Data Kit (ODK) usage, and education on gender-based violence. The outcome shows improved understanding and engagement in digital-based health promotion among participants. This project demonstrates how One Health initiatives can empower communities through interprofessional collaboration and digital tools. Keywords: Digital Literacy, One Health, Gen Z, Gender-based Violence, Community Engagement, Papua, ODK Collect